The Christian Support Networks for Immigrants in Palermo - Marie Bassi (Coordinamento SIBA, 2014)
Based on a fieldwork conducted in Sicily, this paper analyses how, when faced with the emergence of immigration, Christian organisations in Palermo become involved with the migration issue, notably thanks to the pioneering commitment of certain clerics. It draws attention to the heterogeneous nature of the Christian sphere, the internal secularisation of the religious organisations working with migrants, and the transformations of the church-related associative sector from a volunteering to professional expertise model. In sum, the capacity for organisational and ideological adaptation of religious organisations has enabled them to retain social control of the territory by becoming inescapable stakeholders in the migration issue. This study also identifies the practices and the know-how of the actors involved in these organisations, and singles out the motives that lead them to engage with these organisations and the meaning they attach to their implication